The implementation of multicultural-based E-Comic Saleh in strengthening students' character: A case study at SMP N 1 Kaliangkrik Magelang - Mazid, Sukron; Komalasari, Kokom; Abdulkarim, Aim; Rahmat, Rahmat; Wulansari, Atsani (JIPSINDO, 2025)
Character education at the Junior High School (SMP) level is essential in shaping young people who have tolerance, empathy, and respect for diversity. The implementation of multicultural-based e-comic Saleh at Magelang Junior High School is expected to be one of the solutions to strengthen students' character through digital media that is interesting and relevant to their lives. This study aims to evaluate the effectiveness of e-comic Saleh in reinforcing students' character, focusing on multicultural values, including tolerance, empathy, and cooperation. By using a qualitative approach, data were collected from students of grade VII through observation, questionnaire, and interview. The results showed that using e-comic Saleh significantly improved students' understanding of multicultural values and strengthened their positive character. This e-comic was effective in facilitating a more interactive and meaningful learning process. The findings of this research provide important implications for the development of digital learning media in character education in Indonesian schools.